A Prospective Pilot Study of the Safety and Effectiveness of Uterine Artery Embolization for the Treatment of Endometriosis: The UAE-E Study - Koukounaras, Jim; Clements, Warren; Ang, W. Catarina; Zia, Adil; Lukies, Matthew; Moriarty, Heather K; Kavnoudias, Helen (Journal of Clinical Interventional Radiology ISVIR, 2023)
Purpose Uterine artery embolization (UAE) evidence is increasing in the setting of adenomyosis, which shares pathological similarities to endometriosis. Endometriosis is characterized by the presence of endometrium-like tissue outside of the uterus, and the retrograde menstruation hypothesis may account for disease development. In women where fertility is no longer desired, hysterectomy can be offered to improve pain-related symptoms. The authors hypothesize that this cohort of patients may similarly respond to UAE. The aim of this pilot study is to assess the safety and effectiveness of UAE in the management of endometriosis-related symptoms.Methods Six-patient prospective single-arm pilot study in female, premenopausal patients over 40 years with symptoms of endometriosis. Institutional review board approval was obtained.Inclusion criteria include completed family, premenopausal, pelvic endometriosis as confirmed by laparoscopy within the last 5 years, and symptoms of endometriosis impacting quality of life as evidenced by the British Society of Gynaecological Endoscopy pelvic pain and Short Form-36 questionnaires.Results The primary endpoint will be safety, as assessed by the composite number of procedural and postprocedural complications during procedure, predischarge, and at 6 weeks, 3 months, 6 months, and 12 months. Secondary endpoints will include technical success, clinical success, and durability.Discussion This study will be a novel application of UAE in the setting of endometriosis and has the potential to improve patient quality of life. This pilot study will assess safety and allow the investigators to design a prospective randomized controlled study.
Keywords: adenomyosis; endometriosis; pain; chronic; embolization